Health education actions on syphilis with adolescentes: integrative review (Research, Society and Development, 2021)
This study aimed to analyze the scientific evidence on health education interventions for syphilis in adolescents. Integrative review performed in VHL, PubMED, Science Direct and Web of Science databases, no time limit and no restriction on the date when collection started, since the objective was to retrieve as many articles as possible and describing educational actions regarding the prevention of syphilis in adolescents. 1,377 articles were initially identified, but only nine met the eligibility criteria. The literature has shown that educational interventions such as conversation circles, games and workshops on contraceptive methods were effective in actively questioning the participation of adolescents, in addition to being an important opportunity for reflection and discussion, expanding their field of knowledge on these topics. Educational games were the resource most found in studies and with positive results. It is noteworthy that the school is a favorable environment in this dialogue, since, as it is the daily environment of adolescents, where they spend most of the day, they feel safe to express their doubts, fears and feelings. It was concluded that there is a gap in primary studies on the subject that mainly involve adolescents. This highlights the real need for the development and practical application of health education strategies for the prevention of syphilis in adolescence.